Impact of Environmental Turbulence, Self-Esteem and Budget Emphasis on Budgetary Slack - Nur Lazimatul Hilma Sholehah; Parmin Ishak (CV. Rayyan Dwi Bharata, 2022)
This study aims to: (1) Find out how much influence environmental turbulence, self-esteem and budget emphasis have on budgetary slack; (2) Knowing how much environmental turbulence affects budgetary slack; (3) Knowing how much self-esteem affects budgetary slack; (4) Knowing how much influence budget emphasis has on budgetary slack. This type of research is quantitative research. The object of this study was an employee of the Boelamo Regency BKAD. The sampling technique in this study used a saturated sampling method. Data collection was carried out through a survey method using a questionnaire that was distributed directly to all employees in BKAD Boalemo Regency. The results of this study show that (1) Environmental turbulence, self-esteem and budget emphasis simultaneously have a significant effect on budgetary slack, (2) Environmental turbulence has an insignificant positive effect on budgetary slack, (3) Self-esteem has a positive and significant effect on budgetary slack, (4) Budget emphasis has an insignificant positive effect on budgetary slack.